Classification and principal analysis of couplers. Issue 3 (April 2021) - Wang, Zilu
Abstract: Microwave Technology is one of the most of important technologies in history. Microwave technology is developing faster and faster. As we can see, it is very common in our daily life. Microwave technology are used for phone, televisions, security checks and so on, which are all very important in our life. Televisions and mobile phones have become essential devices in every home. It in addition to bring people a relax and cheerful mood, but also is an important communication tool for would news and media opinion. Microwave technology has made a great contribution to our high quality of life and safe travel. With the development of society, microwave will be more and more widely used by people. This paper describes the principle and properties of couplers. The classification of couplers and the principle of couplers are studied by referring to a large number of literatures.